Teaching English as a Foreign Language Application Process. - Santos Palma, Joselyn Yamileth (2024)
The knowledge gained and the tutoring sessions provided by my professor have been crucial in shaping this academic work. This portfolio details the lesson plans and academic essays completed during the various stages of the Curriculum Integration Process, particularly in the design and implementation phases. This project has thoroughly explored the four language skills in TEFL, yielding insights into both theoretical understanding and practical application.